2015
DOI: 10.1039/c5ta03039k
|View full text |Cite
|
Sign up to set email alerts
|

Annealing-induced chemical and structural changes in tri-iodide and mixed-halide organometal perovskite layers

Abstract: Annealing process is crucial in obtaining high-quality perovskite layers used for highly efficient planar perovskite solar cells. In this study, we have investigated annealing-induced chemical and structural changes of tri-iodide (TI) and mixed-halide (MH) organometal perovskite layers using infrared absorption spectroscopy, scanning electron microscopy and x-ray diffraction measurements. For TI layers, the solvent molecule, dimethylformamide (DMF), remained in the form of PbI2/ DMF compound after drying at ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…[ 88 ] Niwano and colleagues later found that upon thermal annealing, both CH 3 NH 3 PbCl 3 and CH 3 NH 3 PbI 3 crystals in mixed-halide perovskite layer were initially formed from an amorphous phase. [ 89 ] Such amorphous phase and MAPbCl 3 crystals served as ions supply for the growth of MAPbI 3 crystals when the MA and chloride ions were evaporated from the mixed-halide perovskite layer, resulting in a thin layer composed of large MAPbI 3 grains.…”
Section: Thermal Annealingmentioning
confidence: 99%
“…[ 88 ] Niwano and colleagues later found that upon thermal annealing, both CH 3 NH 3 PbCl 3 and CH 3 NH 3 PbI 3 crystals in mixed-halide perovskite layer were initially formed from an amorphous phase. [ 89 ] Such amorphous phase and MAPbCl 3 crystals served as ions supply for the growth of MAPbI 3 crystals when the MA and chloride ions were evaporated from the mixed-halide perovskite layer, resulting in a thin layer composed of large MAPbI 3 grains.…”
Section: Thermal Annealingmentioning
confidence: 99%
“…On the other hand, short-term annealing of 15 minutes of trihalide perovskites does not improve the crystallinity of the perovskite film in Figure 4(a). A recent study by Ma and colleagues concluded that the crystallinity is influenced by the volatility of DMF used in the formation of PbI 2 solution [22]. Further, they suggest that using a mixed halide solution will add excess chloride ions that help improve crystallinity and morphology.…”
Section: Annealing Temperature and Timementioning
confidence: 99%
“…Excess chlorine ions may form the chloride-containing amorphous phase that melts at around 100 ∘ C in mixed halide perovskite layers. During prolonged annealing, the "melted amorphous phase with highly moveable ions may supply ions needed for the growth of MAPbI 3 crystals" [22]. The evaporation of excess ions, methylammonium and chloride, promotes the transformation of MAPbCl 3 from MAPbI 3 .…”
Section: Annealing Temperature and Timementioning
confidence: 99%
See 1 more Smart Citation
“…Organometal halide perovskites (OHPs) have the chemical structure ABX 3 (A: organic cation, B: metal cation, and X: halide anion) and have been used as efficient active layers in perovskite solar cells (PeSCs) . The control of the X‐site halide composition in OHPs affects their electrical characteristics including the bandgap energy, perovskite structure, and film morphology . The X‐site halide can be composed of two different halide ions, i.e., I − and Cl − ions, yielding a mixed‐halide perovskite, CH 3 NH 3 PbI 3− x Cl x .…”
Section: Introductionmentioning
confidence: 99%